Short-term mechanical support with the Impella 5.x for mitral valve surgery in advanced heart failure - protected cardiac surgery - Oßwald, Anja; Shehada, Sharaf-Eldin; Zubarevich, Alina; Kamler, Markus; Thielmann, Matthias; Sommer, Wiebke; Weymann, Alexander; Ruhparwar, Arjang; El Gabry, Mohamed; Schmack, Bastian (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Surgical treatment of patients with mitral valve regurgitation and advanced heart failure remains challenging. In order to avoid peri-operative low cardiac output, Impella 5.0 or 5.5 (5.x), implanted electively in a one-stage procedure, may serve as a peri-operative short-term mechanical circulatory support system (st-MCS) in patients undergoing mitral valve surgery. Methods: Between July 2017 and April 2022, 11 consecutive patients underwent high-risk mitral valve surgery for mitral regurgitation supported with an Impella 5.x system (Abiomed, Inc. Danvers, MA). All patients were discussed in the heart team and were either not eligible for transcatheter edge-to-edge repair (TEER) or surgery was considered favorable. In all cases, the indication for Impella 5.x implantation was made during the preoperative planning phase. Results: The mean age at the time of surgery was 61.6 ± 7.7 years. All patients presented with mitral regurgitation due to either ischemic (n = 5) or dilatative (n = 6) cardiomyopathy with a mean ejection fraction of 21 ± 4% (EuroScore II 6.1 ± 2.5). Uneventful mitral valve repair (n = 8) or replacement (n = 3) was performed via median sternotomy (n = 8) or right lateral mini thoracotomy (n = 3). In six patients, concomitant procedures, either tricuspid valve repair, aortic valve replacement or CABG were necessary. The mean duration on Impella support was 8 ± 5 days. All, but one patient, were successfully weaned from st-MCS, with no Impella-related complications. 30-day survival was 90.9%. Conclusion: Protected cardiac surgery with st-MCS using the Impella 5.x is safe and feasible when applied in high-risk mitral valve surgery without st-MCS-related complications, resulting in excellent outcomes. This strategy might offer an alternative and comprehensive approach for the treatment of patients with mitral regurgitation in advanced heart failure, deemed ineligible for TEER or with need of concomitant surgery.
Veröffentlicht: 11. Juli 2023
Gesehen am 26.09.2023